2008
DOI: 10.1051/0004-6361:200810734
|View full text |Cite
|
Sign up to set email alerts
|

Interacting and merging galaxies from the second Byurakan survey

Abstract: We present new results from HI observations of 53 previously undetected interacting and merging galaxies from the Second Byurakan Survey (SBS), in which 30 systems have been detected (detection rate 56%). High-resolution gray-scale optical images and isophotal maps of the HI detected galaxy systems are presented, in addition to comments on these systems. The possibility of confusion arising from known objects within the telescope beam is discussed for each case. For nine unconfused mergers, global HI parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…pairs) in xGASS had a factor of two higher f gas than isolated central galaxies of the same stellar mass. Other surveys that have reported elevated H i gas fractions in mergers include Casasola et al (2004), Huchtmeier et al (2008) and Jaskot et al (2015). Conversely, based on a sample of dwarf galaxy pairs, Stierwalt et al (2015) found H i gas fractions consistent with their control sample.…”
Section: Comparison With Previous Resultsmentioning
confidence: 97%
“…pairs) in xGASS had a factor of two higher f gas than isolated central galaxies of the same stellar mass. Other surveys that have reported elevated H i gas fractions in mergers include Casasola et al (2004), Huchtmeier et al (2008) and Jaskot et al (2015). Conversely, based on a sample of dwarf galaxy pairs, Stierwalt et al (2015) found H i gas fractions consistent with their control sample.…”
Section: Comparison With Previous Resultsmentioning
confidence: 97%
“…High molecular gas fractions may follow from the increased central surface densities that precede starbursts in mergers. Indeed, several previous observational studies have measured increased gas fractions in either atomic or molecular gas (Braine & Combes 1993;Bettoni et al 2001;Huchtmeier et al 2008;Stark et al 2013;Goncalves et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite well documented SFR enhancements in this same sample (Scudder et al 2012;Patton et al 2013), Fertig et al (2015) do not detect any decline in the HI gas fraction of close pairs. Indeed, in an earlier study based on a small sample of confusion-free HI measurements, Huchtmeier et al (2008) suggested that mergers may be relatively HI-rich. Casasola et al (2004) present a similar study, but with over 1000 galaxies drawn from all interaction stages, from well separated pairs to coalesced remnants.…”
Section: Introductionmentioning
confidence: 99%
“…Galaxy 1200 (PGC035568) has very blue g − r 0 and is in catalogues of both emission line galaxies/UV excess galaxies (Markarian & Stepanian 1983) and BCDs (Thuan et al 1999), and is Huchtmeier et al (2008). It is another extremely metal-poor galaxy (Morales-Luis et al 2011).…”
Section: Galaxy 1200; Sdssj11320262+5722366mentioning
confidence: 99%